GMA special - Laaro, Cheche (Quezon City Probe Productions, 1988)
A one hour program on GMA-7 on the occasion of the inauguration of its tower at Quezon City. Focuses on the philosophy, crews policy and the people who have worked in the network for over 25 years.
VHS.
Keywords: GMA-7 (Television station : Quezon City).